Mycobacterium bovis ESAT-6, CFP-10 and EspC antigens show high conservation among field isolates. (July 2018) - Encinas, M.; Marfil, M.J.; Garbaccio, S.; Barandiaran, S.; Huertas, P.; Morsella, C.; Macías, A.; Magnano, G.; Zapata, L.; Bigi, F.; Cataldi, A.; Paolicchi, F.; et al.
Abstract: ESAT-6, CFP-10 and EspC are virulence factors that have been extensively assayed for bovine and human tuberculosis diagnosis due their potent T-cell inducing activities. While polymorphisms of ESAT-6 and CFP-10 were analyzed, with the description of CFP-10 variants in M. tuberculosis, this fact has not been explored in M. bovis field isolates. The coding sequences of esxA (ESAT-6), esxB (CFP-10) and mb3645c (EspC) from 58 M . bovis strains exhibiting genomic variability (spoligotyping) were analyzed. Two genes – esxA and esxB – remained invariant while mb3645c exhibited one synonymous polymorphism (G to A mutation, position 66bp) in one isolate, compared to M. bovis AF2122/97 reference strain. All isolates exhibited a synonymous nucleotide polymorphism simultaneously (G to A mutation, position 255bp), compared to M. tuberculosis H37Rv reference strain. This study confirms the high conservation for ESAT-6, CFP-10 and EspC in local M. bovis field isolates and reinforce the use of these three antigens in the diagnosis of bovine tuberculosis. Further studies should be performed to globally confirm these findings.